PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR - Raturayawan; Muhammad Yahya; Abdul Muis Mappalotteng (UNM Journal of Technology and Vocational, 2025)
This study aims to develop interactive learning media for the Computer and Network Basics subject at SMK Swasta Salusiampek using the Research and Development (R&D) method. This media was developed as a solution to the limitations of conventional learning, which remains theoretical and lacks interactivity. The evaluation was conducted through validation by media experts, material experts, and student respondents using Likert and Guttman scales to measure the effectiveness, attractiveness, and ease of use of the media. The evaluation results indicate that the interactive learning media achieved an average score of above 85%, demonstrating excellent quality in terms of design, navigation, material relevance, and student engagement. This media has been proven to enhance student involvement and understanding of network topology and the OSI model through simulation, animation, and self-assessment features. However, some challenges were identified, such as limited internet access, low teacher digital literacy, and insufficient school hardware. To address these issues, it is recommended to provide teacher training, develop an offline version, and improve school technological infrastructure. Thus, this interactive learning media has the potential to be an innovative solution in enhancing learning quality in the digital era and preparing vocational students to face the growing demands of the industrial world.